TASHQI IQTISODIY FAOLIYATNI MAMLAKATIMIZDA YANADA TAKOMILLASHTIRISH - Misirov Asliddin; Suyunova Sevinch Lutfullayevna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract.  This  article  analyzes  the  state  of  foreign  economic  activity  of  the Republic of Uzbekistan and provides proposals and recommendations for its further development and improvement. The issues of integration with the world economy, increasing  export  potential,  attracting  foreign  investments,  and  stimulating  foreign economic activity through improving the system of customs and tax incentives are covered. Also, the article, based on the analysis of existing problems, considers the directions  of  liberalization  of  foreign  trade  policy  and  production  of  competitive products.